Impact of foreign direct investment on economic growth in CEE countries - Alua Salykbayeva (Theoretical Hypotheses and Empirical Results, 2023)
This paper examines the impact of foreign direct investment (FDI) on economic growth in 16 countries of Central and Eastern Europe (CEE). It provides an analysis of the existing economic development literature, especially focusing on the effect of inward FDI on economic growth of CEE countries for the period between 1991 and 2010. In addition, such important variables in the context of economic development as level of education, initial GDP per capita, the interaction terms between FDI and human capital (level of education), and the interaction term between FDI and initial GDP per capita are going to be discussed in detail and how they can affect economic growth of the CEE countries. The empirical part of the project is going to be divided into two types of econometric analysis: OLS linear regressions model and Dynamic Panel Data (DPD): Arellano-Bond linear dynamic panel data estimations.